Indian national identity and foreign policy re-evaluating the career of K. M. Pannikar (1894-1963) - Elli, Mauro; Paolini, Rita (Security, conflict and cooperation in the contemporary world, 2023)
Shedding light on the role of India within twentieth-century international relations, this book explores the life and career of Kavalam Madhava (K. M.) Panikkar (1894-1963), an Indian historian, statesman and diplomat. Having been involved in Indian intellectual and political life throughout the transition from the British Empire to the Nehruvian era, Panikkar was an important figure in the evolution of the modern Indian state. Based on over four years of extensive research both in India and Europe, and the analysis of public writings and unpublished archival documents, this book examines Panikkar's role in the Indian national movement, the governance of several Princely states, and India's foreign policy, notably with China. Not only do the authors critically re-evaluate Panikkar's intellectual and political thoughts, but also his influence on the broader issue of India's path towards independence. Offering a valuable contribution to modern Indian diplomatic history and wider international relations, this comprehensive book emphasises Panikkar's importance in shaping the modern idea of India and crucial elements of Indian foreign policy.-